Regulatory Compliance and Associated Quality of Amoxicillin in Drug Retail Outlets of Southwestern Ethiopia - Aman A (Dove Medical Press, 2021)
Abdella Aman,1 Gemmechu Hasen,1,2 Hayder Usman,1 Sultan Suleman1,2 1School of Pharmacy, Institute of Health, Jimma University, Jimma, Oromia, Ethiopia; 2Jimma University Laboratory Drug Quality (JuLaDQ), Jimma, Oromia, EthiopiaCorrespondence: Gemmechu HasenSchool of Pharmacy, Institute of Health, Jimma University, PO Box 378, Jimma, Oromia, EthiopiaEmail gemmechuhasen2009@gmail.com; gemmechu.godena@ju.edu.etBackground: While the research findings confirm the existence of private drug retail outlets that do not comply with regulatory standards in many low-income countries, there are a lack of reports that evaluate the quality of medicines obtained from these firms. Therefore, the aim of this study was to evaluate the regulatory compliance of the retails and associated quality of amoxicillin in Southwestern Ethiopia.Methodology: Forty-two drug retail outlets in Jimma town were evaluated using an inspection checklist developed by the Ethiopian regulatory authority, and dispensers from these retail outlets were interviewed using the pretested structured questionnaire. The drug outlets were coded and categorized into noncompliant and compliant drug retail outlets. The physicochemical quality of amoxicillin capsules obtained from these retail outlets were evaluated following methods described in the US Pharmacopoeia.Results: The present study revealed that about 54.76% drug retail outlets were compliant with the regulatory standard. Factors like income of retail outlet, experience of dispenser, and training regarding good storage practice were associated with status of regulatory compliance (p-value < 0.05). The identification, dissolution, and assay results indicated that all amoxicillin samples obtained from both noncompliant and compliant drug retail outlets complied with pharmacopoeial specification limit. Besides, the independent unequal variance t-test revealed that there is no significant difference between mean dissolution and assay of API of the amoxicillin samples obtained these drug retail outlets (p-value > 0.05).Conclusion: The regulatory compliance of private drug retail outlets in Jimma town is not satisfactory. Moreover, the laboratory findings revealed that all samples of amoxicillin capsules compiled with pharmacopoeial specifications acceptance for packaging and labeling information, identification, assay, and dissolution. However, despite the fact that assays of the amoxicillin from retail outlets are within the required specification, the assays of amoxicillin obtained from noncompliant retail outlets appears to be slightly degraded, which may potentially demonstrate the impact of noncompliance of the drug retail outlets on the quality of medicines.Keywords: drug retails, regulatory compliance, quality, amoxicillin, Ethiopia